The caretaker : a novel - Rash, Ron, 1953- (Doubleday, 2023)
"It's 1951 in Blowing Rock, North Carolina. Blackburn Gant, his life irrevocably altered by a childhood case of polio, seems condemned to spend his life among the dead as the sole caretaker of a hilltop cemetery. It suits his withdrawn personality, and the inexplicable occurrences that happen from time to time rattle him less than interaction with the living. But when his best and only friend, the kind but impulsive Jacob Hampton, is conscripted to serve overseas, Blackburn is charged with caring for Jacob's wife, Naomi, as well. Sixteen-year-old Naomi Clarke is an outcast in Blowing Rock, an outsider, poor and uneducated, who works as a seasonal maid in the town's most elegant hotel. When Naomi eloped with Jacob a few months after her arrival, the marriage scandalized the community, most of all his wealthy parents, who disinherited him. Shunned by the townsfolk for their differences and equally fearful that Jacob may never come home, Blackburn and Naomi grow closer and closer until a shattering development derails numerous lives. A tender examination of male friendship and rivalry as well as a riveting, page-turning novel of familial devotion, The Caretaker brilliantly depicts the human capacity for delusion and destruction all too often justified as acts of love"--